Strategi Optimalisasi Produksi Pangan Lokal Desa Tes Kabupaten Timor Tengah Utara - Febrya Christin Handayani Buan; Dian Grace Ludji; Meri Helsiana Mata; Andreas Kefi; Azor Yulianus Tefa; Ebenhaiser Liunokas; Eva Binsasi; Nugraha Kristiano Floresda Dethan; Kristoforus Wilson Kia; Fried Markus Allung Blegur (Jurnal SOLMA, 2026)
Background: The optimization implemented for the partner group KWT Kasih Setia in Tes Village represents an intervention in the marketing strategy of local food products. The marketing system, previously largely conventional, was improved through strengthened branding, the design of a graphic brand identity, and the implementation of digital sales data management. This intervention aimed to expand market reach and contributed to increased partners’ income. Methods: The community service program (PkM) was implemented through counseling and direct mentoring, systematically designed using a participatory learning-by-doing approach to optimize capacity building for the target partners. Results: The results showed a significant improvement based on the paired t-test. This improvement was reflected in the partners’ ability to strengthen branding, design brand and packaging identities, and utilize a digital sales data management dashboard. Conclusions: The community service program (PkM) for KWT Kasih Setia in Tes Village proved effective in enhancing partners’ capacity in branding, packaging design, and digital sales data management, thereby expanding marketing reach and sustainably increasing income.